2009
DOI: 10.1111/j.1753-4887.1974.tb06329.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Hemorrhagic Sweet Clover Disease Iv. The Isolation and Crystallization of the Hemorrhagic Agent

Abstract: 1. The hemorrahgic agent is spoiled sweet clover hay (Melilotus alaba) has been isolatd in a pure state, m. p. 288‐289°, from experimentally produced spoiled hays as well as form hyas that killed cattle in argicultural practice. 2. This substance has the empirical formula C12H12O6. It is optically inactive. There are two acidic hydroxyls in the molecule. The acidity of the pure substance falls between that of the phenols and the carboxylic acids. A crystalline dimethyl other C12H12O4(OCH2)2 with a melting poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…1 This compound is used for the prevention and treatment of thrombosis. Furthermore, dicoumarol derivatives exhibit bioactivity as inhibitor of reductases.…”
Section: Introductionmentioning
confidence: 99%
“…1 This compound is used for the prevention and treatment of thrombosis. Furthermore, dicoumarol derivatives exhibit bioactivity as inhibitor of reductases.…”
Section: Introductionmentioning
confidence: 99%
“…This is derived from the observation that the incidence of osteoporotic fracture is relatively lower in regions of the country where dietary intake of natto is high. (23) There are also some suggestions that the anti-osteoporotic effects of MK 4 are independent of g-carboxylation.…”
mentioning
confidence: 99%
“…(24) In a recent meta-analysis of 13 small randomized controlled trials with data on bone loss, the authors concluded that supplementation with either MK 4 or K 1 has a positive effect on BMD. Further analysis, including only the trials that provided both BMD and fracture data, concluded that supplementation with 45 mg/d of menatetrenone was associated with increased BMD and reduced fracture incidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hemorrhagic factor isolated from sweet clover was first described in an article published in 1940. 2 One year later, the identity of this hemorrhagic agent was characterized, and the first anticoagulant, dicumarol, was discovered. 3 The first branded form of warfarin, developed by the Wisconsin Alumni Research Foundation, was approved by the FDA on June 8, 1954.…”
mentioning
confidence: 99%